A population-based surveillance study on severe acute maternal morbidity (near-miss) and adverse perinatal outcomes in Campinas, Brazil: The Vigimoma Project - Cecatti José; Sousa Maria; Luz Adriana G; Surita Fernanda; Souza João; Amaral Eliana; Campbell Oona (BMC, 2011)
Abstract Background Auditing of sentinel health events based on best-practice protocols has been recommended. This study describes a population-based investigation on adverse perinatal events including severe acute maternal morbidity (near-miss), maternal and perinatal mortality, as a health intervention to help improve the surveillance system. Methods From October to December 2005, all cases of maternal death (MD), near-miss (NM), fetal deaths (FD), and early neonatal deaths (END), occurring in Campinas, Brazil, were audited by maternal mortality committees. Results A total of 4,491 liveborn infants (LB) and 159 adverse perinatal events (35.4/1000 LB) were revised, consisting of 4 MD (89/100.000 LB) and 95 NM (21.1/1000 LB), 23.7 NM for each MD. In addition, 32 FD (7.1/1000 LB) and 28 END (6.2/1000 LB) occurred. The maternal death/near miss rate was 23.7:1. Some delay in care was recognized for 34%, and hypertensive complications comprised 57.8% of the NM events, followed by postpartum hemorrhage. Conclusion Auditing near miss cases expanded the understanding of the spectrum from maternal morbidity to mortality and the importance of promoting adhesion to clinical protocols among maternal mortality committee members. Hypertensive disorders and postpartum hemorrhage were identified as priority topics for health providers training, and organization of care.